Construction of Yeast Pichia pastoris Expressing the Recombinant p53 as a Secreted Protein into Culture - Nga, Tran Thi Thuy; Hoa, Nguyen Quang; Tuyen, Hoang Van; Tuyen, Do Thi; Thai, Dinh Nho (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: Human p53 protein has been known as a tumor suppressor and described as "the guardian of the genome", referring to its role in conserving stability of genome by preventing mutation. The recent studies on p53 protein expression have demonstrated the important role and effectiveness of exogenous p53 protein in tumor suppression. In the world, the expression of p53 for therapeutically interest was extensively study but in Vietnam it has not been noticed. In the other hand, Pichia pastoris showed a good expression system for many exogenous proteins with a simple cloning work and cheap culture. In this study, codon optimization of gene encoding human p53 protein was performed for suitable expression in Pichia pastoris yeast. It was designed as construct of p53 fused with TAT and His-tag sequences (TAT-p53-His). The construct was cloned into pPICZαA expression vector by using EcoR I and Xba I enzymes to make pPICZαA-TAT-p53-His. Yeast strains containing genes coding for TAT-p53-His was obtained. The integration of TAT-p53-His construct into yeast genome was verified by using PCR with AOX1 primers. The expression of the recombinant TAT-p53-His in the culture of P. pastoris X33 was confirmed by SDS-PAGE. Keywords: Pichia pastoris, gene expression, p53, codon optimization.